Strengthening the Profile of Pancasila Students through the Differentiated Mulia Method - Rahayuningsih, Puji; Harahap, Nasrudin; Warisno, Andi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
Characteristics of community and the school environment are starting point for determining vision, mission, and goals. Facing these problems and the results of the diagnostic assessment that has been carried out on all school residents, this program considers differentiation that is adjusted to talents, interests, and abilities as well as the personalities of all school residents. This study aims to achieve school’s vision and mission so that can strengthen the Pancasila Student Profile. The method applied is Mulia Differentiated Method as an abbreviation of Mulia, Superior, Literate, Inspirational, and Adaptive. Differentiation because this program is adjusted to diagnostic assessment carried out at the beginning of the school year which is carried out on all school residents, so that this program is adjusted to talents, interests, abilities, and personalities. The results state that the Mulia strategy that we implemented brought benefits to the school, students, guardians, parents, the committee and the community around the school. The benefits for the school community are the creation of a religious and family atmosphere, the beauty of the school environment becomes a comfortable and safe place.